Analisis Kesiapan Praktek Lapangan Industri (PLI) Mahasiswa Departemen Teknik Elektro Universitas Negeri Padang - Muhamad Ridwan; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to provide an overview of the preparation of students from the Department of Electrical Engineering to carry out the Industrial Field Practice program. The method in this research uses a quantitative descriptive method, meaning that this research method aims to express a picture or description of an objective that is arranged using numbers, starting from data collection, interpretation of the data obtained, and the appearance of the research results. The instrument in this research used a questionnaire that was distributed to students. Each statement item on the instrument is assessed using a Likert scale. The data analysis used is a quantitative descriptive approach using averages, standard deviation values​​, and score categories one to five to determine the extent of data distribution. The results of this research indicate the level of readiness of Electrical Engineering Department students in implementing the Industrial Field Practice program. Several indicators have the same category level, namely the cognitive readiness indicator is in the sufficient category, the affective readiness indicator is in the sufficient category and the psychomotor readiness indicator is also in the sufficient category. So, it can be concluded that the level of readiness of Electrical Engineering Department students to carry out the Industrial Field Practice program can be interpreted as being quite ready as measured by 3 readiness indicators.